Efektivitas Komunikasi Digital Instagraam @kemendukbangga_bkkbn Program Quick Win: Dengan Pendekatan Social Media Engagement - nelly nuroniah; Rika Utari; Jazil Nusaf Aini; Tria Patrianti; Sa'diyah El adawiyah (Jurnal Public Relations (J-PR), 2026)
This study aims to evaluate the effectiveness of Instagram digital communication of the National Population and Family Planning Agency (BKKBN) in supporting the Quick Win Stunting prevention Program through a social media engagement approach. The study used a descriptive qualitative method with digital observation of Instagram accounts @kemendukbangga_bkkbn the period June-November 2025 and analysis of supporting documents. The results of the study show that BKKBN Instagram is effective in increasing the reach and public awareness of stunting issues, characterized by the high number of views, especially from non-follower audiences. However, the engagement that is formed is still dominated by engagement at the cognitive level and has not developed optimally towards affective and behavioral involvement, as can be seen from the stagnation of follower growth and the lack of dialogical interaction. The dominance of working-age and female audiences shows the relevance of the message to policy objectives, but the low involvement of men signals the need for more effective communication strategies. Viewed from the perspective of Two-Way Symmetrical Communication, BKKBN's Instagram communication still tends to be one-way and informative. This study concludes that the success of government digital communication is not only determined by the reach of the message, but also by the quality of continuous dialogical engagement to encourage changes in stunting prevention behavior.